Penggunaan Jilbab: Pandangan Islam dan Relevansinya terhadap Pendidikan Moral di Indonesia Dalam Bingkai Media - Salmah Sahari Harahap; Ali Sati; Anas Habibi Ritonga (Ittishol: Jurnal Komunikasi dan Dakwah, 2023)
Education is one of the forums for developing the character of the nation's children, who have morals and are in line with the state's expectations. Various pioneers in the world of education have emerged along with the times, especially in attribute issues. The hijab is one of the identities and obligations that women must obey to use the hijab in the school environment. As a democratic country, the use of the hijab is considered as a right to freedom of use or not under the pretext of a democratized state. As a result, the use of the hijab in schools in Indonesia raises pros and cons. Coercion of the use of the hijab is considered intolerance and violates human rights. Viewed from an Islamic point of view, the hijab is a protector for every woman and an attribute in shaping good morals.